Looking behind the curtain: a model of left behind places and feelings - Tobias Johannes Hertrich; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2024)
The concept of “left behind” places is complex and multidimensional. It encompasses economic factors, demographic aspects, infrastructure and connectivity criteria, social factors, political and cultural aspects. Previous studies on the concept have only described the feeling of left behind very superficially. We therefore focus on the feeling of left behind. We show how individual feelings can become a regional phenomenon of left behind. The feeling of left behind is primarily fed by two components that are felt by many people in left behind places: autonomy deficit and low appreciation. Causes and suitable political measures for left behind places are derived from our conception. – – Das Konzept der left behind places ist komplex und multidimensional. Es umfasst wirtschaftliche Faktoren, demografische Aspekte, Infrastruktur- und Konnektivitätskriterien, soziale Faktoren, politische und kulturelle Aspekte. Frühere Studien zu diesem Konzept haben das Gefühl des Zurückgelassenwerdens nur sehr oberflächlich beschrieben. Wir konzentrieren uns daher auf das Gefühl des Zurückgelassenwerdens. Wir zeigen, wie individuelle Gefühle zu einem regionalen Phänomen des Zurückgelassenwerdens werden. Das Gefühl des Zurückgelassenwerdens speist sich vor allem aus zwei Komponenten gespeist, die von vielen Menschen an zurückgelassenen Orten empfunden werden: Autonomiedefizit und geringe Wertschätzung. Ursachen und geeignete politische Maßnahmen für zurückgebliebene Orte werden aus unserer Konzeption abgeleitet.
Keywords: O18; O20; R11; R12; 330; case study; feeling left behind; left behind place; lagging region; regional development; policy measures